2023
DOI: 10.1186/s40478-023-01597-8
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-induced damage to the fimbria/fornix reduces hippocampal-prefrontal cortex connection during early abstinence

Laura Pérez-Cervera,
Silvia De Santis,
Encarni Marcos
et al.

Abstract: Introduction Alcohol dependence is characterized by a gradual reduction in cognitive control and inflexibility to contingency changes. The neuroadaptations underlying this aberrant behavior are poorly understood. Using an animal model of alcohol use disorders (AUD) and complementing diffusion-weighted (dw)-MRI with quantitative immunohistochemistry and electrophysiological recordings, we provide causal evidence that chronic intermittent alcohol exposure affects the microstructural integrity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…58 Notably, it has been demonstrated that chronic substance use such as alcohol exposure affects white matter microstructural integrity, leading through disturbed functional connectivity to decreased cognitive flexibility in rats. 59 A possible explanation for the involvement of our highlighted white matter regions in sustaining inhibition abilities in SUD populations could reside in its links to functional connectivity, as previously suggested in patients with hypertension. Our most striking result was the relation between white matter integrity and the momentary expression of inhibition abilities, sustaining its impact on subsequent use.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…58 Notably, it has been demonstrated that chronic substance use such as alcohol exposure affects white matter microstructural integrity, leading through disturbed functional connectivity to decreased cognitive flexibility in rats. 59 A possible explanation for the involvement of our highlighted white matter regions in sustaining inhibition abilities in SUD populations could reside in its links to functional connectivity, as previously suggested in patients with hypertension. Our most striking result was the relation between white matter integrity and the momentary expression of inhibition abilities, sustaining its impact on subsequent use.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, white matter integrity has been observed to constrain resting‐state network organization, strength 57 and even adaptation 58 . Notably, it has been demonstrated that chronic substance use such as alcohol exposure affects white matter microstructural integrity, leading through disturbed functional connectivity to decreased cognitive flexibility in rats 59 . A possible explanation for the involvement of our highlighted white matter regions in sustaining inhibition abilities in SUD populations could reside in its links to functional connectivity, as previously suggested in patients with hypertension 60 …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has repeatedly shown that especially inflammation - related genes are up-regulated in alcohol dependence 4648 . And furthermore, that neuroinflammatory processes indeed promote AUD development and progression 49, 50 . Consequently, the role of anti-inflammatory approaches is suggested to be particularly promising as for AUD treatment 51 .…”
Section: Discussionmentioning
confidence: 99%